A META analysis and systematic review of the effects of exercise interventions on middle-aged and elderly patients with depression - Zheng Zhang; Jia-Yun Liu; Kai-Tuo Zhu; Gui-Quan Huo (PLoS ONE, 2025)
Objective This study sought to conduct a meticulous systematic review, delving into the efficacy of exercise interventions on depressive symptoms among middle-aged and older adults. Additionally, we aimed to scrutinize the nuanced influence of various intervention factors on the intricate relationship between exercise and depressive symptoms within this demographic. Methods Our investigation involved an extensive search across multiple databases, including PubMed, Embase, Web of Science, and the Cochrane Library, spanning from the inception of these repositories to December 2023. Following a rigorous screening process, we identified and included 12 papers, encompassing a total of 994 subjects. Results The meta-analysis unveiled a compelling overall effect size of exercise interventions on depressive symptoms in middle-aged and older individuals, represented by SMD = -0.41, with a 95% confidence interval of [-0.60, -0.22], and P < 0.0001. This statistical evidence underscores the significant and positive impact of exercise interventions on ameliorating depressive symptoms in this demographic. However, a degree of heterogeneity among studies was observed, with I2 = 48% and P = 0.03. Conclusion The comprehensive synthesis of outcomes elucidates the pronounced positive effect of exercise interventions in enhancing depressive symptoms among middle-aged and older adults. Specifically, the gentle and balanced exercise series emerges as particularly efficacious in mitigating depression. Furthermore, individual exercises stand out as more effective, with optimal results noted for moderate exercise sessions lasting 30 to 60 minutes. Our findings also highlight the superiority of short-term interventions, followed by medium- and long-term exercise interventions, in terms of efficacy. Nevertheless, recognizing the inherent heterogeneity and potential limitations of our study, we advocate for future large-scale, comprehensive investigations to validate these findings. Additionally, optimizing exercise intervention protocols necessitates a more nuanced understanding, urging further research endeavors to refine strategies aimed at improving depressive symptoms in middle-aged and older adults.